2018
DOI: 10.1177/0961203318801520
|View full text |Cite
|
Sign up to set email alerts
|

The anti-thrombotic effects of vitamin D and their possible relationship with antiphospholipid syndrome

Abstract: The importance of the immunomodulatory effects of vitamin D has recently been associated with autoimmune and chronic inflammatory diseases. Vitamin D deficiency has been linked to the development of autoimmune conditions. Antiphospholipid syndrome is an autoimmune disease characterized by thrombotic events and obstetric complications in patients with antiphospholipid antibodies. Current data show that patients with antiphospholipid syndrome have a high prevalence of vitamin D deficiency even without classic ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 67 publications
(91 reference statements)
2
13
0
Order By: Relevance
“…In accordance with previous studies, low levels of complement C3 were observed in 28% of all OAPS patients (45, 199, 200). Interestingly, 39.5% of the patients in the vitamin D deficient and 57.1% in the vitamin D insufficient presented low levels of C3, suggesting an association between lower levels of vitamin D and lower levels of C3, indicative of complement consumption/activation by autoantibodies.…”
Section: Observational Study: Vitamin D Levels In Women With Obstetrisupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with previous studies, low levels of complement C3 were observed in 28% of all OAPS patients (45, 199, 200). Interestingly, 39.5% of the patients in the vitamin D deficient and 57.1% in the vitamin D insufficient presented low levels of C3, suggesting an association between lower levels of vitamin D and lower levels of C3, indicative of complement consumption/activation by autoantibodies.…”
Section: Observational Study: Vitamin D Levels In Women With Obstetrisupporting
confidence: 92%
“…Data from seventy-six pregnant women with OAPS were analyzed. In agreement with the literature (45, 84, 199, 200), a high percentage (77.6%) of these patients showed hypovitaminosis D (Table 1). Within this group, 64.4% of the women were vitamin D deficient and 35.6% vitamin D insufficient in the first trimester of pregnancy.…”
Section: Observational Study: Vitamin D Levels In Women With Obstetrisupporting
confidence: 91%
“…A much stronger case can be made though for a protective effect of vitamin D against thrombotic complications of the anti‐phospholipid syndrome [101], and here there are intriguing parallels with the thrombotic tendency in COVID‐19 [102]. Studies have shown a prevalence of up to 70% for vitamin D deficiency amongst patients with anti‐phospholipid syndrome and meta‐analysis of 4 case–control studies including 325 cases and 507 controls showed an odds ratio of 3.06 ( P < 0.001) for frequency of vitamin D deficiency in patients with anti‐phospholipid syndrome [103].…”
Section: Vitamin D Deficiency Lupus Anticoagulant‐associated Thrombomentioning
confidence: 99%
“…The central role of inflammation in aPL-mediated thrombosis underpins the potential of vitamin D in treating APS patients since it possesses numerous immunomodulatory properties. 92 Among its many effects, the ability of vitamin D to inhibit TLR4/MyD88 signaling, 93,94 TF expression 88 endothelial activation, and inflammation and cell perturbation play crucial roles in obstetric as well as thrombotic APS. 95,96 An in-vitro study demonstrated that vitamin D modulates signalling through TF/PAR-2, indicating that it could potentially limit TF/PAR-2 mediated placental inflammation and subsequent adverse outcomes in APS pregnancies.…”
Section: Adjunctive Therapiesmentioning
confidence: 99%